UPAYA MENINGKATKAN PRESTASI BELAJAR PADA KONSEP SUHU DAN KALOR DENGAN MENGGUNAKAN METODE INQUIRI KELAS X MIA 2 SMA NEGERI 1 PINANGSORI TAHUN PELAJARAN 2016/2017 - Hotma Saritua Tarihoran (Universitas Muhammadiyah Tapanuli Selatan, 2018)
his scientific paper is the class action Research in an attempt to improve the learning results of SMAN 1 Pinangsori Regency Central Tapanuli made using the learning method of Enquiries. Research activities carried out at SMA Negeri 1 Pinangsori and chose the class X MIA 2 with the number of 41 people that consists of 19 students are male and 22 female students. After learning by using learning methods, there are Enquiries increased significant learning results. After done action in cycle I, the average value of the results of learning students rose to 68.30 (still in the low category), while the average failure (student behavior that does not comply with learning activities) amounted to 31.70 %. Then in cycle II, i.e. after the tackle in action as a reflection of the I-cycle average value of students rose to 97.56% approaching the category of good that did not pass the 2.44% or 1 person, rate completeness students increased from 68.30% become 97.56%. Similarly changes the activity of students, there has been an increase in the interest and willingness of students learn physics. The increasing presence of average students characterizes it, a growing number of students who complete the task on time and the students many who dare to put forward opinions and solve them well. Keywords: The achievements of the Study, methods of Enquiries.